Research on the Scientific Development of Online Education Network Ecosystem - Sun, Wei; Godz, Natalia; Liu, Xuemin (My University, 2022)
This paper analyzes the various manifestations, and the causes which contribute to the online education network ecological crisis, further clarifies the relationship between the development of the network, and human society. Recommendation, and measures which can be applied to the scientific development of the online education network ecosystem was also included in the paper.
Keywords: online education; online ecosystem; sustainable development; network ecosystem